The Legal Nature of the Operator’s Liability in Law No. 9 Of 2023 Regulating The Operation of Self-Driving Vehicles in the Emirate of Dubai - Rashid , Aisha (Journal of Legal Sciences, 2025)
Recent developments in self-driving vehicles have become one of the most important issues that must be researched, especially with regard to civil liability arising from accidents involving these vehicles. With the issuance of Law No. 9 of 2023 regarding the regulation of the operation of self-driving vehicles in the Emirate of Dubai, as it is the first law to regulate this activity in the Arab world, it is a new activity in our contemporary reality which is extremely complex due to the intertwining of the relationships of the parties influencing its subject, so the law required studies to clarify the aims of its regulation and provisions in a way that reveals the approach followed by its legislator. It has become necessary to search within the details of this law for several issues, the most important of which is the civil liability arising from accidents of these vehicles, analyzing and criticizing them to determine their legal nature, since the law did not allocate more than one article which is Article 14, to the judgement of civil liability, in addition to searching for the nature of the operator of self-driving vehicles. The research followed the descriptive approach within the limits of defining self-driving vehicles, the analytical approach within the limits of defining the nature of the operator, and the critical approach in revealing the operator's responsibility in the law of operating self-driving vehicles, in three sections, and in the conclusion, it reached several results and recommendations, the most important of which was the issuance of an executive regulation for Law No. (9) of 2023 regarding the regulation of operating self-driving vehicles in the Emirate of Dubai, detailing its provisions and implementation.